2014
DOI: 10.1108/imds-02-2013-0076
|View full text |Cite
|
Sign up to set email alerts
|

Business social networks and academics' entrepreneurial intentions

Abstract: Purpose – This study analyses the role of social networks and their effects on academics' entrepreneurial intentions (AEI), from an academic cognitive perspective. Specifically, the paper investigates how business (distinguishing between industrial and financial links) and personal social networks, through opportunity-relevant information and support, could influence academics' intentions to start a business venture on the basis of their research knowledge. The paper examines the mediator roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 110 publications
3
37
1
Order By: Relevance
“…The conceptual framework of this model suggests that 41.2% of the variance of AEI has surpassing the explained variance in previous studies on AE. (Fernández-Pérez et al, 2014). The theme of AEI is a very interesting, yet a little explored area of the research.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptual framework of this model suggests that 41.2% of the variance of AEI has surpassing the explained variance in previous studies on AE. (Fernández-Pérez et al, 2014). The theme of AEI is a very interesting, yet a little explored area of the research.…”
Section: Discussionmentioning
confidence: 99%
“…The result strongly contrasted with existing entrepreneurship research on BIs as significant business partners during the startup and development of new and sustainable entrepreneurial ventures through training and mentorship. Social networks also offered unique privileges to BIs and clients by expediting business processes to save time amid decision-making issues (Fernandez-Perez et al, 2013). The formal and informal partnerships with private firms and NGOs or government institutions and universities provided access to the overall support needed from mentors and business partners during the incubation and post-incubation phases (Alpenidze et al, 2019).…”
Section: Evaluation Of the Findingsmentioning
confidence: 99%
“…Sometimes research focuses on detailed issues e.g. individuals' personality in this context (Wang and Yang 2007), business networks of academics (Fernándes-Pérez et al 2014) or knowledge sharing through institutional repositories on campus (Kim and Ju 2008). Recently the role of technological channels of communication has been analysed, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Spanish studies, factors such as personal and professional profile, institutional variables and social networks had a very positive influence on knowledge sharing. Furthermore, business networks of academics played a crucial role in their entrepreneurial intentions and engagement in commercially oriented fields of research (Padilla-Meléndez and Garrido-Moreno 2012;Fernándes-Pérez et al 2014). Swedish studies revealed that there is a reciprocal relationship between information and communication technologies and the ways in which information is used and shared.…”
Section: Literature Reviewmentioning
confidence: 99%